Monitoring and discussion on river carbon and nitrogen fluxes in the Pearl River Estuary region - Dawei Li; Hongji Liang; Zimiao Zhao; Huifeng Huang; Cuiming Li; Chengzhi Wang (Heliyon)
Rivers link land and sea, playing an important role in the global carbon and nitrogen cycles. By conducting surveys and research on river flow in a specific region, we can gain a better understanding of the nitrogen and carbon sinks in the area and their contributions to the environment. In this study, we conducted bi-annual sampling and monitoring of river flow in the Pearl River Delta downstream of Zhuhai, China, and collected hydrological information. The results show that the total flow in the dry season (939.22 m3/s) is lower than that in the rainy season (1556.40 m3/s); the highest concentration of total organic carbon is in the dry season (14.70 mg/L) and the lowest is in the rainy season (10.95 mg/L); the total organic carbon emission flux is lower in the dry season (1804.45 g/s) than in the rainy season (3331.04 g/s), and the maximum emission points in both seasons are at the Damenkou Waterway, with values of 2327.60 g/s and 917.87 g/s, respectively; the highest concentration of total nitrogen is in the dry season (40.20 mg/L) and the lowest is in the rainy season (17.80 mg/L); the total nitrogen flux is lower in the dry season (2204.68 g/s) than in the rainy season (2403.47 g/s). Inorganic nitrogen is the main component of total nitrogen, and ammonium nitrogen is the main component of inorganic nitrogen. The maximum flux of total nitrogen at both sampling frequencies is in the main entrance waterway. Same as the maximum flux point of carbon emissions, the main reason is that this point has the highest flow rate in this survey, which further proves that it is the river that needs the most attention for pollution control. By referring to historical statistical data and combining it with the results of this survey, we can provide data support for the next phase of pollution control in surrounding waters.